An Analysis of Verbal and Nonverbal Communication Skill - Amanda, Aulia; Lestari, Indah (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2024)
Mata Najwa is a talk show program broadcasted by Metro TV in an interview format. In every interview, the interviewer's communication skills play an important role in determining the success of the program. Effective communication techniques on television aim to dig up information and provide entertainment, so that good communication skills are needed so that the interview runs smoothly and is interesting for the audience. The topics raised in the Mata Najwa program provide inspiration and insight to the audience. This program is considered to have higher quality than other talk shows, with various themes covering social, economic, and inspirational aspects. This study focuses on the episode